Lactobacillus plantarum in the Gut of a Marine Fish from a Caloocan Local Market - Nieves L. Capili; Jose Mallari (Advanced Gut & Microbiome Research)
The search for potential probiotic bacteria of value to medicine, food industry, agriculture, and aquaculture has been extended in this study where bacterial isolates from the intestines of talakitok (Alectis sp.), a Philippine marine fish cultured and grown using de Man-Rogosa-Sharpe agar, were used to isolate Gram-positive rods that are catalyse negative. Its identity of 93-95% with Lactobacillus plantarum strains was confirmed by NCBI BLAST of the 16S rRNA forward and reverse sequences.